Kreasi pertunjukan teater berbasis etnomatematika terintegrasi nilai-nilai islam di sekolah dasar - Irna Khaleda Nurmeta; Luthfi Hamdani Maula; Synta Agustri; Marisha Amelia Ramadhan; Fauziah Husni (Universitas Sebelas Maret, 2024)
This research is entitled Garap Performing Arts Ethnomathematics Theater Integrated with Islamic Values in Elementary Schools, which aims to describe the performance process that is part of the Art Work Degree program at SD Negeri Cicadas Cisaat Kab. Sukabumi. To explore the data, the Project Based Research method is used, namely research based on previous projects that have been carried out by the school and then become special notes for researchers to improve and package the project to be made. The findings of the research consisted of four aspects, namely diagnosing the problem found that the previous performance was held in the classroom and packaged by dubbing. Planning was made by researchers by recommending Children's Theater performances that combine several branches of art (drama, music, dance). Implementation of the plan took the form of a partial and combined training process. The evaluation of the activity was the presentation of a Children's Theater performance in front of a public audience.